Health-Related Behaviour of Students of Federal College of Agriculture, Animal Health and Production Technology, Ibadan (2004)
The emphasis on health services is shifting from curative measures and hospital-based care to preventive behaviour that promotes health. This new approach involves every member of the society. A study of 132 students of the Federal College of Agriculture and Animal Health and Production Technology, Ibadan was carried out to investigate their health-related behaviour. Health related behaviours are steps taken to preserve one's own health and avoidance of detrimental behaviours. One hundred and eighteen (89.39%) of the students engage in sporting activities. Only 6.06%, 9.85%, 24.24% and 10.61% of the students smokers, drinks alcohol, drinks coffee and chews Kolanut respectively. Majority of the Students (78.03%) live a stress-free life. This result shows that only a few of the students exhibits negative health-related behaviour while the majority has positive-related behaviour. It was recommended that positive attitudes and healthy lifestyles should be encouraged among students of tertiary institutions in Nigeria.